Martin, Céline, Larrea, Juan José (eds.): Nouvelles chartes visigothiques du monastère pyrénéen d’Asán (Scripta Mediævalia, 42). Burdeos, Ausonius Éditions, 2021, 256 pp. [EAN: 9782356133717] - Martín Viso, Iñaki (Studia Historica. Historia Antigua, 2021)